從儒家生命倫理的角度反思中國大陸的衛生保健制度改革: Health Care System Reforms in Mainland China: A Confucian Appraisal - CAO, Yongfu (International Journal of Chinese & Comparative Philosophy of Medicine, 2007)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 本文在分析中國大陸衛生保健制度改革的背景和措施的基礎上，提出了人們對該項改革“普遍不滿意”的觀點，並認為改革中缺乏儒家生命倫理的價值指導，是導致人們“普遍不滿意”的一個深層次原因。 本文認為，在儒家看來，“醫乃仁術”，儒家倫理與衛生保健是天然地結合在一起的﹔ “儒醫同道”也是中國古代醫界的一個傳統﹔中國儒家生命倫理有著豐富的內涵：例如“責人”思想，即尊重人、重視人的生命﹔“不忍” 思想，即同情病人﹔“博愛”，即“ 愛人”、“ 泛愛眾”﹔“推己及人”思想等。 最後，文章認為要使中國衛生保健制度改革獲得成功，使人們滿意，必須明確“ 仁”是衛生保健制度的價值核心，只能把“ 市場”作為手段、不能作為目的﹔必須認識到， 建立良好的衛生保健制度是政府義不容辭的責任，這才是符合儒家的“仁政”思想的， 而醫生和醫院是衛生保健制度中“醫乃仁術”的最終實現者。挖掘儒家生命倫理，並指導衛生保健制度改革， 也許能夠使中國衛生改革和發展走上“健康”道路。 On the basis of analyzing the health care system reforms in mainland China in recent years, this paper argues that it was the absence of a direction from Confucian bioethics that should have, been responsible for major problems encountered in the reform as well as for the general dissatisfaction of the people with the results of the reforms. From the viewpoint of Confucian morality,"medicine is the art of benevolence (ren)." Confucian ethics naturally supports proper health care. The idea that "Confucianism and medicine share the same principle" is integrated in the tradition of conventional Chinese medical world. Confucian bioethics has abundant connotations. For example, the thought that "min gui" (the people as valuable) means that government ought to respect the people and cherish people’s lives; the thought of "ce ying" (sympathy) implies that the physician should be compassionate with the patient; and "ci bei" (philanthropy) means that one should love every individual. These types of Confucian thought should be drawn on to guide medical practice. Most of all, it should be noted that benevolence (ren) is the core value of a health care system. In order to render the reform successful, this core value must be upheld. Health care markets should be established and regulated to contribute to the core value of benevolence. Doctors and hospitals are the performers of medicine as the art of benevolence. Confucian bioethics, as the guidance of health care system reforms, may help Chinese health care reforms develop healthily. DOWNLOAD HISTORY | This article has been downloaded 22 times in Digital Commons before migrating into this platform.